Elements for a posthuman fashion : la sperimentazione dei videomaker e dei fashion designer di Showstudio - Alfieri, Alessandro (Scenari, 2021)
SHOWStudio. The home of fashion film and live fashion broadcasting is a web-project dedicated to the world of fashion system, with materials from the world of fashion of different nature (like exclusive interviews and previews of the seasons of the most important brands and fashion maisons). However, the most characteristic production of the site, directed and founded by photographer and videomaker Nick Knight, are the fashion films, experimental short films that upset the traditional categories of the fashion world, launching the post-human imagination in the world of fashion. The post-human has contaminated, by the Alexander McQueen revolution, the fashion design and the cultural industry sectors, highlighting how the post-human dimension today assumes an undeniable seducing, investable function also and above all in the commercial sphere.